Network-based approaches for evaluating ambient assisted living (AAL) technologies. (April 2017) - Gomersall, Tim; Nygård, Louise; Mihailidis, Alex; Sixsmith, Andrew; Hwang, Amy S.; Hedman, Annicka; Astell, Arlene
Ambient assisted living technologies could support people experiencing physical or cognitive challenges, to maintain social identities and complex activities of daily living. Although there has been substantial investment in developing ambient assisted living innovation, less effort has been devoted to understanding how to evaluate the impact of ambient assisted living on physical and mental health. Taking a theory-based evaluation approach, we suggest firstly that ambient assisted living technologies rely on networks of people and organizations to function, and secondly, analysing the changing structure of networks can bridge the gap between socio-technological change and individual-level capabilities. We present conceptual arguments for taking a network perspective in ambient assisted living evaluations, illustrated with examples from our own group's work on technology use among older people with cognitive impairments. We then discuss the different types of network-based evaluation approaches available, their theoretical assumptions, and the sort of research questions they could address.